Students’ lateral mathematical thinking ability on trigonometric problems - M E Nggaba; T Herman; S Prabawanto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
To describe students' lateral mathematical thinking ability on trigonometricproblems, we conducted a research on 30 students (15/16 year old) in West Java, Indonesia.This research is a qualitative descriptive research and data collection technique is written testwith 3 description questions. The test results were analyzed using three indicators of lateralmathematical thinking ability, (1) finding different ways of looking at things, (2) identifyingthe dominant ideas of the problems, and (3) associating concepts / ideas into several strategiesmay be true or false. Results of the study showed that: (1) almost one-third of the number ofstudents can look for different ways of looking at a problem, (2) more than one-third ofstudents can identify the dominant ideas of the problem, and (3) more than half students canassociate a concept / idea so that it becomes some strategies that may be true or false. Based onthe result of research, it is seen that most students do not have good lateral thinking ability insolving trigonometric problems.